129k views
4 votes
Let f(x) = -4x + 7 and g(x) = 2x - 6. Find (gof) (1)

2 Answers

6 votes


(g\circ f)(x)=2(-4x+7)-6=-8x+14-6=-8x+8\\\\(g\circ f)(1)=-8\cdot1+8=0

User Michael Mahn
by
5.5k points
1 vote

Answer:

(gof) (1) = 0

Explanation:

f(x) = -4x + 7

g(x) = 2x - 6

(gof) (1)

First find f(1)

f(1) = -4(1) + 7

f(1) = -4+7=3

Then put 3 in for x in g(x)

g(f(1) = 2(f(1))-6

= 2 (3) -6

= 6 -6

= 0

User Eduard Sukharev
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.